2012
DOI: 10.4041/kjod.2012.42.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arch form between ethnic Malays and Malaysian Aborigines in Peninsular Malaysia

Abstract: ObjectiveTo determine and compare the frequency distribution of various arch shapes in ethnic Malays and Malaysian Aborigines in Peninsular Malaysia and to investigate the morphological differences of arch form between these two ethnic groups.MethodsWe examined 120 ethnic Malay study models (60 maxillary, 60 mandibular) and 129 Malaysian Aboriginal study models (66 maxillary, 63 mandibular). We marked 18 buccal tips and incisor line angles on each model, and digitized them using 2-dimensional coordinate system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 17 publications
3
32
2
1
Order By: Relevance
“…The outcomes of this study are also in line with those of Al-Khateeb and Abu Alhaija, [7] Asiry and Hashim [16] and Ling and Wong, [17] in that there was a tendency for female subjects to have narrower upper and lower dental arch widths than males at the interpremolar and intermolar regions. At the same time, the current results differ from those reported by Nojima et al [6] and Othman et al [14] who reported no significant differences across racial groups in terms of dental arch dimensions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The outcomes of this study are also in line with those of Al-Khateeb and Abu Alhaija, [7] Asiry and Hashim [16] and Ling and Wong, [17] in that there was a tendency for female subjects to have narrower upper and lower dental arch widths than males at the interpremolar and intermolar regions. At the same time, the current results differ from those reported by Nojima et al [6] and Othman et al [14] who reported no significant differences across racial groups in terms of dental arch dimensions.…”
Section: Discussioncontrasting
confidence: 99%
“…On reviewal of the results, there was no significant gender dimorphism between the male and female groups regarding both the upper and lower intercanine widths. The same finding was reported by Diwan and Elahi [2] and Younes [13] in Saudi and Egyptian samples, and Othman et al [14] for Malaysians. However, this was not true for the results found by Al-Khateeb and Abu Alhaija, 9 in Jordanians, and Sarhan and Diwan [15] in Egyptian and British samples.…”
Section: Discussionsupporting
confidence: 88%
“…This is contrary to a few reports by Kook et al (2004), Radmer and Johnson (2008) and Nojima et al (2001) where they all had found signifi cant differences inter-canine arch width between Korean, North American white, Afro-American, Caucasian residing in Japan and Japanese. Latest study by Othman et al (2012) had strongly suggested that different race group should have some basic difference on arch width and shape. Unfortunately, this was not seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Keseimbangan dan keharmonisan dari proporsi wajah pada umumnya akan memberikan bentuk wajah yang ideal. 5 Selain itu, bentuk wajah yang ideal dipengaruhi juga oleh bentuk lengkung gigi. Lengkung gigi dapat dijadikan sebagai faktor yang penting dalam perawatan ortodonti.…”
Section: Pendahuluanunclassified